Record of a Pennsylvanian-Cisuralian marine transgression, southern Bolivia: A short-lived event in western Gondwana? - Di Pasquo Lartigue, Maria (2017)
Largely terrestrial Pennsylvanian strata (Macharetí and Mandiyutí groups) in Bolivia and northern Argentina contain a brief marine incursion. Dominated by glacio-fluvial and glacial diamictites, much of the thick succession is peri-glacial in origin and deposited within a basin with paleohighs. In southernmost Bolivia (Balapuca section), new discoveries of poorly preserved orthotetacean brachiopods (Derbyoides sp.) document the marine systems. Without the brachiopod, co-occurrence of numerous in situ gastropods (Mourlonia balapucense), with all ontogenetic growth stages, could not be confirmed as marine. Palynomorphs corresponding to the TB Zone di Pasquo stratigraphically below the megafossil occurrence place the age of the assemblage in the Kasimovian/Gzhelian Stage. Many units show extensive recycling of Devonian and Mississippian palynomorphs (Retispora lepidophya, and others) and a brachiopod demonstrate pre-Gzhelian erosion and high energy deposition in diamictites during deposition of the Tarija Formation, and through much of the succession. This brief marine transgression in this basin corresponds to regionally more long-lived marine transgressions in western Argentina, characterized by the Tivertonia-Streptorhynchus Fauna (Moscovian-Gzhelian) linked with the beginning of a global major sea level rise as an interlude in the Gondwana glaciations. The marine transgression exceeded isostatic rebound. Further in Bolivia, the transgression from the north produced the Copacabana Formation carbonates. Coeval siliciclastics of the San Telmo Formation in the south show contrasting in lithologic facies and faunal composition as a result of thermal barriers (warm – cold waters).